The Relationship between Impulse Buying and Post-Purchase Regret Online in Women Users of Beauty Products - Sendi Ayu; Abdul Aziz (Universitas Negeri Semarang, 2024)
The ease of access to online purchases often leads to post-purchase regret when the products do not meet expectations. One of the most frequently purchased items by women is beauty products. The wide variety of beauty products available requires consumers to make careful choices. However, purchase decisions are sometimes made impulsively, leading to regret. This study is a correlational quantitative research. The sampling technique used is purposive sampling, with a sample of 307 women who use beauty products. The data collection method involved the use of instruments, including a 24-item impulse buying scale and a 27-item valid post-purchase regret scale. The reliability coefficient for the impulse buying scale is 0.954, and for the post-purchase regret scale, itis 0.868. The data analysis used is Spearman’s Rho, with a significance value (p) of 0.000 and a correlation coefficient (r) of 0.355. The analysis results indicate that impulse buying falls into the low category, while post-purchase regret is in the medium category. Therefore, it can be concluded that the hypothesis proposing a relationship between impulse buying and post-purchase regret in women using beauty products is accepted. This means the higher the impulse buying, the higher the postpurchase regret in women using beauty products.